If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -20)(8d + -6) = 0 Reorder the terms: (-20 + 8x)(8d + -6) = 0 Reorder the terms: (-20 + 8x)(-6 + 8d) = 0 Multiply (-20 + 8x) * (-6 + 8d) (-20(-6 + 8d) + 8x * (-6 + 8d)) = 0 ((-6 * -20 + 8d * -20) + 8x * (-6 + 8d)) = 0 ((120 + -160d) + 8x * (-6 + 8d)) = 0 (120 + -160d + (-6 * 8x + 8d * 8x)) = 0 Reorder the terms: (120 + -160d + (64dx + -48x)) = 0 (120 + -160d + (64dx + -48x)) = 0 (120 + -160d + 64dx + -48x) = 0 Solving 120 + -160d + 64dx + -48x = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-120' to each side of the equation. 120 + -160d + 64dx + -120 + -48x = 0 + -120 Reorder the terms: 120 + -120 + -160d + 64dx + -48x = 0 + -120 Combine like terms: 120 + -120 = 0 0 + -160d + 64dx + -48x = 0 + -120 -160d + 64dx + -48x = 0 + -120 Combine like terms: 0 + -120 = -120 -160d + 64dx + -48x = -120 Add '48x' to each side of the equation. -160d + 64dx + -48x + 48x = -120 + 48x Combine like terms: -48x + 48x = 0 -160d + 64dx + 0 = -120 + 48x -160d + 64dx = -120 + 48x Reorder the terms: 120 + -160d + 64dx + -48x = -120 + 48x + 120 + -48x Reorder the terms: 120 + -160d + 64dx + -48x = -120 + 120 + 48x + -48x Combine like terms: -120 + 120 = 0 120 + -160d + 64dx + -48x = 0 + 48x + -48x 120 + -160d + 64dx + -48x = 48x + -48x Combine like terms: 48x + -48x = 0 120 + -160d + 64dx + -48x = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(15 + -20d + 8dx + -6x) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(15 + -20d + 8dx + -6x)' equal to zero and attempt to solve: Simplifying 15 + -20d + 8dx + -6x = 0 Solving 15 + -20d + 8dx + -6x = 0 Move all terms containing d to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -20d + 8dx + -15 + -6x = 0 + -15 Reorder the terms: 15 + -15 + -20d + 8dx + -6x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -20d + 8dx + -6x = 0 + -15 -20d + 8dx + -6x = 0 + -15 Combine like terms: 0 + -15 = -15 -20d + 8dx + -6x = -15 Add '6x' to each side of the equation. -20d + 8dx + -6x + 6x = -15 + 6x Combine like terms: -6x + 6x = 0 -20d + 8dx + 0 = -15 + 6x -20d + 8dx = -15 + 6x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 6*x=64-2x | | 15/x-4=2/x | | 4x^2+18x=22 | | Sin(2x)tan(x)-tan(x)=0 | | 2^n=5/4 | | knx=3/2 | | k(x)=2f(-2x)-1 | | 5(x-2)=12x | | 4+6n=10 | | 5+(-2)=5+2 | | 6x^2-x-61=0 | | -225+7r=755 | | 15+3=9x | | 3+(-4)=3-4 | | 2|2|-5|-4|/|-4•2| | | 5-4x=3-6x | | 5x-ry=-9 | | 5x-15y=-20 | | 23=x/6(-32) | | 14x-x^2-49=0 | | 21-b=2b | | 16x^2+8x^2= | | 16x^2+4x^2= | | x(x)-8x+8=0 | | 9/3[6*4/8] | | X=4y-y^6 | | x*log(X)=3000 | | X^2-4x+4+y^2+2y+1=9 | | 5x^2+3x-120=0 | | 12-2/5x=4 | | 5y-12=x | | 6(x-3)=5x-1 |